Can Antisperm Antibodies affect Male Fertility after Subinguinal Varicocelectomy ? A Local Study - Ehab Jasim Mohammad; Duraid Taha Abdulkareem; Omar Aziz Hassan (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Antisperm Antibodies researches emerged in 1899 in a report referring to the ability of spermsto be antigenic in case of injection into a foreign species. In 1900, researchers showed that sperms are alsoantigenic in case of injection into similar species. Moreover, Wilson (1954) identified ASAB in the partnersof infertile male and then observed the association of ASAB with male infertility. In addition, a correlationwas found between ASAB and sperm proteomics, and thus researchers specified those ASABs decreasingmale fertilities via inhibition of the sperm functions crucial for fertilization.Objectives: The study aimed at evaluating the effect(s) of varicocelectomy on the anti-sperm antibody incases who suffer from varicocele.Methods: In the present prospective, controlled, clinical research which has been performed during theperiod from april 2015 to may 2020. Therefore, the blood samples have been randomly provided from190 males with mean age 33 years (ranging from 20-45 years) ,with the clinical varicocele who have beenindicated for varicocelectomy. Then, participants have been randomly selected from the urology outpatientclinic of Al-Yarmouk Teaching Hospital in Baghdad,Iraq,and Al-Ramadi Teaching Hospital and privateclinic.Results: In our study, ASA level (27.2%) with the positive serum ASA prior to with those (43.2%) followingthe operation demonstrated a significant difference statistically (p = 0.033). However, such a result has beennot confirmed in the patients (27.4%) with positive semen ASA prior to with those (31.3%) following thesurgical operation (p = 0.881).Conclusion: According to the results, varicocelectomy did not have any impact on the semen ASA,despite,but serum antibody enhanced following varicocelectomy and sperm motility improved. Therefore,varicocelectomy usefully affected the semen parameters in the infertile men suffering from varicocele.